2020
DOI: 10.3899/jrheum.200903
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in Men With Psoriatic Arthritis: A Population-based Cohort Study

Abstract: Objective To define the incidence of erectile dysfunction (ED) in a population-based cohort of men with psoriatic arthritis (PsA). Methods Data pertaining to demographics, ED, and potential confounding diagnosis were extracted from a comprehensive medical record system for a population-based cohort of men with PsA and an age-matched male comparator cohort. Cumulative incidence of ED adjusted for competing risk of death was compared between the two cohorts. Results There were 128 age-matched pairs of men with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…In our study, when compared to the patients with and without PsA, only family history of PsA and CRP levels were different which were higher in patients with PsA than those without. These ndings were consistent with the literature (14) (15). No signi cant difference was observed in patients with and without PsA in terms of age, gender, PsO duration, presence of comorbidities, PASI score, PsO subtypes in patients with and without PsA in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, when compared to the patients with and without PsA, only family history of PsA and CRP levels were different which were higher in patients with PsA than those without. These ndings were consistent with the literature (14) (15). No signi cant difference was observed in patients with and without PsA in terms of age, gender, PsO duration, presence of comorbidities, PASI score, PsO subtypes in patients with and without PsA in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Higher TurPAS and EARP scores in patients with PsA than those without in our study were also expected ndings. In Lopez-Medina study, while polyarticular involvement was the dominant feature of PsA (60%), mono-oligoarthritis was observed in 40%, enthesitis in 45.8%, dactylitis in 37% and axial involvement in 35.5% in patients with PsA (15). In our study, although oligo-monoarticular subtype was the most frequent involvement, other manifestations were similar to the former study.…”
Section: Discussionsupporting
confidence: 87%
“…In the literature on psoriasis, SD is more prevalent in women than in men [ 8 , 9 , 25 ], but we observed mild and relatively more frequent impairment in the male group with PsA. A cohort study found an increased risk of erectile dysfunction (ED) in men with PsA, but likely underpowered due to the small number of cases [ 26 ].…”
Section: Discussionmentioning
confidence: 78%
“…In their animal experiment, Carneiro et al [20] showed that rats developed endothelial dysfunction and cavernosal smooth muscle hypercontractility after infusion of TNF-α. Similarly, Wilton et al [21] reported an increase in proinflammatory cytokine gene expression (IL-1b, IL-6 and TNF-a) and macrophage infiltration in the major pelvic ganglion in a rat model in which they induced ED through bilateral cavernous nerve damage. In another study, it was revealed that overexpression of IL-6 and TNF-α in the corpus cavernosum tissue caused ED in Type 2 diabetic rats [22].…”
Section: Discussionmentioning
confidence: 85%